Plantar pressure and EMG activity of simulated and actual ski jumping take-off - Virmavirta, M.; Komi, P. V. (Scandinavian Journal of Medicine & Science in Sports, 2001)
Plantar pressures and activation of the four muscles (VL - vastus lateralis, GL - gluteus, TA - tibialis anterior and GA - lat. gastrocnemius) were measured from ten ski jumpers under simulated laboratory conditions with training shoes (Lab TS) and with jumping boots (Lab JB) as well as in actual hill jumping conditions (Hill). The most significant differences between measured conditions were found in muscle activation patterns and plantar pressures prior to take-off. The centrifugal force due to the curvature of the inrun under actual hill jumping conditions caused extra pressure under the fore and rear parts of the feet (P<0.001) and therefore higher activation in all muscles (P<0.001 for VL, TA and GA and P<0.01 for GL). The actual take-off was characterized by high pressure under the toes during the early phase and high pressure under the heel during the latter phase of take-off. However, this should probably he interpreted as a commonly used improper technique where the balance during take-off is not well maintained to allow effective force production. Activation of GA, especially with regard to anteroposterior pressure distribution under the feet, differed significantly between the measured conditions. The role of GA for explosive force production during ski jumping take-off is much smaller as compared to that of the knee and hip extensor muscles.